Evaluation of Electrolytes Disturbances in Iraqi Chronic Myeloid Leukemia Patients treated with Nilotinib with Monitoring of Response by FISH Study (Baghdad Science Journal, 2015)
Chronic myeloid leukemia (CML) is a myeloproliferative disorder characterized by the presence Philadelphia chromosome (Ph) which was created by a reciprocal translocation between chromosomes 9 and 22 (t [9;22] [q34;q11]. The approval of the 2nd generation TKI ( Nilotinib) takes the treatment of CML patients into new erea with more efficiency and mild to moderate adverse effects. This study was aimed at evaluation of molecular cytogenetic response by (FISH) for Nilotinib in Iraqi patients with assessment for electrolytes disturbances of Nilotinb by measuring a panel of electrolyte (Na+, K+, Ca++, PO4--- and Mg++) , where thirty Iraqi patients with CML who have resistance or no response to Imatinib treatment, attending to Baghdad Teaching Hospital/Hematology Department, have been submitted to this study. Blood samples have been taken pre and post starting treatment with Nilotinib, FISH study was done only for CML patients, while 30 normal healthy control volunteers submitted to the same panel of electrolytes measurements (Na+, K+, Ca++, PO4--- and Mg++) in addition to pre and post treatment Nilotinib patients. The results show out of 30 patients (17) males and (13) females with male to female ratio 1.3:1, FISH results for patients (pre and post) treatment mean±SD were(58.7%±26.2 % and 45.7%±29.9%) obviously significant with good cytogenetic response in resistance CML for Imatinib. Sodium levels in mmol/L pre, post treatment and control mean±SD were (139.2±6.9 , 142.4±9.2 and 140.4±2.52) respectively, with no significant difference between each other with P value > 0.05 in all comparisons. Potassium levels mean±SD in mmol/L results for patients (pre, post) and control were (4.6±0.69, 4.3±0.68 and 4.46±0.76) respectively, with no significant difference between each other with P value > 0.05 in all comparisons. Calcium levels in mg/dL results for patients (pre, post) and control as mean±SD were (8.68 ±1.68, 8.1±1.72 and 9.12±0.38) respectively with no significant differences except between post treatment and control group with P value > 0.05 in all comparisons. Phosphate levels in mg/dL results for patients (pre, post) and control as mean±SD were (2.5±0.84, 2.95±1.04 and 3.4±0.49) respectively with significant difference with P value < 0.05 in all comparisons. Magnesium levels in mg/dL results for patients pre, post and control as mean±SD were (1.93±0.34, 2.06±0.44 and 2.1±0.34) respectively with no significant difference between each other with P value > 0.05 in all comparisons. This study sheds a light on the molecular cytogenetic response for CML patients who have already resistance to Imatinib and Nilotinib that has much more potent effect as approved by studies and this study has used FISH technique. This study emphasizes on the importance of evaluation of electrolyte panel for CML patients before starting Nilotinib study taking in to consideration if these patients are already receiving Imatinib which can also affect bone metabolism and calcium and phosphate levels.